Control of Disruptive Behavior in an Elementary Classroom: Two Case Studies - Munro, Barry C. (Canadian Journal of Counselling and Psychotherapy, 2012)
Two case studies are presented to illustrate a novel approach to the development of appropriate in-class behavior in two primary-grade boys who were characterized as problem cases (hyperactive, uncooperative) by school personnel. A signalling device and counter were used by which the experimenter was able to provide immediate reinforcement for appropriate behavior. This resulted in a marked decrease in the rate of inappropriate behavior and an increase in the amount of on-task time over the period of investigation. A desirable side effect accompanying this increased task control was a change of social behavior. It was observed that both boys tended to interact more with their classmates and teachers in an appropriate fashion. The results suggested the apparatus could be a useful addition to the repertoire of school personnel for the modification of inappropriate classroom behavior.